Genetics of membranous nephropathy. Issue 9 (6th November 2017) - Gupta, Sanjana; Köttgen, Anna; Hoxha, Elion; Brenchley, Paul; Bockenhauer, Detlef; Stanescu, Horia C; Kleta, Robert
Abstract: An HLA-DR3 association with membranous nephropathy (MN) was described in 1979 and additional evidence for a genetic component to MN was suggested in 1984 in reports of familial MN. In 2009, a pathogenic autoantibody was identified against the phospholipase A2 receptor 1 (PLA2 R1). Here we discuss the genetic studies that have proven the association of human leucocyte antigen class II and PLA2 R1 variants and disease in MN. The common variants in PLA2 R1 form a haplotype that is associated with disease incidence. The combination of the variants in both genes significantly increases the risk of disease by 78.5-fold. There are important genetic ethnic differences in MN. Disease outcome is difficult to predict and attempts to correlate the genetic association to outcome have so far not been helpful in a reproducible manner. The role of genetic variants may not only extend beyond the risk of disease development, but can also help us understand the underlying molecular biology of the PLA2 R1 and its resultant pathogenicity. The genetic variants identified thus far have an association with disease and could therefore become useful biomarkers to stratify disease risk, as well as possibly identifying novel drug targets in the near future.